Electric machinery - Fitzgerald, A.E.; Kingsley, Charles; Umans, Stephen D. (New Delhi : Tata McGraw-Hill, 2005)
Engineering
Keywords: Electric Machinery; Magnetic circuits; Transformers; Rotating machines; Synchronous machines; Power electronics; Speed control; DC machines